Pengembangan Media Joyful Reading dalam Meningkatkan Kemampuan Membaca Awal Anak Usia 5-6 Tahun - Rahmi, Novia; Kurnia, Rita; Satria, Defni (UIN Sultan Maulana Hasanudin Banten, 2026)
Mobile technology's quick development tends to promote broader usage, particularly when it comes to preschool education. The goal of this project is to provide Joyful Reading materials that will enable children at Pembina 1 Pekanbaru State Kindergarten, ages 5 to 6, develop their basic reading abilities. This study was motivated by the large number of kids who struggle with early reading skills, including the inability to read simple words, recognize letters, and discern letter sounds, as well as the usage of less engaging and conventional learning materials. Research and development (R&D) utilizing the ADDIE model—analysis, design, development, implementation, and evaluation—was the methodology employed in this work. Small-scale testing, expert validation, interviews, and observation were used to gather data. According to the findings, the Joyful Reading media was rated as